Marketing digital para la Microempresa Silvia Ochoa en la ciudad de Babahoyo en el periodo 2024. - Robelli Torres, Ileana Eleonor (2025)
This case study analyzes the marketing strategies used by the Silvia Ochoa microenterprise in the city of Babahoyo, to attract and retain customers in the year 2024. Three specific objectives were determined: the bases of Digital Marketing and customer acquisition, analyze the preferences of the consumers of the Silvia Ochoa microenterprise, and explore E-Marketing strategies to promote customer loyalty. The methodology included a review of the literature on digital marketing and conducting surveys and interviews with the microenterprise's clients. The results indicated that Silvia Ochoa lacks a solid presence on social networks, limiting her visibility and interaction with her clientele. Although it uses WhatsApp as the main communication channel, it is not present on other social networks such as Facebook, TikTok and Instagram, which reduces its ability to attract new customers. The analysis concluded that digital marketing is essential for the competitiveness of microbusinesses, allowing them to differentiate themselves and maintain effective relationships with their customers. Despite operating since 2006 in the personal care and aesthetics sector, the company faces significant challenges in its digitalization. Therefore, it is suggested to implement a digital marketing plan that includes the active use of social networks, targeted advertising and direct communication strategies, with the aim of improving your visibility in the market and strengthening the loyalty of your customers.